Long-Term Lumateperone Treatment in Bipolar Disorder: Six-Month Open-Label Extension Study. (April 2023) - Tohen, Mauricio; Durgam, Suresh; Kozauer, Susan; D'Souza, Ian; Chen, Richard; Mates, Sharon
Abstract: Introduction: Approved therapeutics for bipolar depression are associated with a range of undesirable side effects. Lumateperone (LUMA), a mechanistically novel antipsychotic that simultaneously modulates serotonin, dopamine, and glutamate neurotransmission, is FDA-approved for the treatment of schizophrenia and depressive episodes associated with bipolar I or bipolar II disorder. The efficacy of LUMA in bipolar depression was previously established in two Phase 3 trials, as monotherapy (NCT03249376) and as adjunctive to lithium or valproate (NCT02600507). A recent Phase 3 multi-center trial, Study 401 (NCT02600494) investigated the efficacy and safety of LUMA in bipolar depression and comprised a 6-week, randomized, double-blind, placebo-controlled period and a 6-month open-label extension (OLE) period. Here, we report the results of the OLE period, examining long-term safety. Methods: Patients, aged 18–75 years, with a clinical diagnosis of bipolar I or II disorder who were experiencing a major depressive episode (Montgomery-Åsberg Depression Rating Scale [MADRS] Total score ≥20 and a Clinical Global Impression Scale-Bipolar Version, Severity [CGI-BP-S] score ≥4) were eligible for Study 401. Patients who completed the double-blind study were eligible for direct rollover into the OLE or were re-screened if completing the double-blind period prior to the initiation of the OLE. During the OLE, LUMA 42 mg was administered once-daily in the evening for 25 weeks. The primary objective was safety and tolerability of LUMA as measured by incidences of adverse events (AEs) and changes in laboratory parameters, cardiometabolic measurements, electrocardiogram (ECG), and vital signs. The secondary objective was improvement/maintenance of symptoms of depression as measured MADRS and CGI-BP-S Total scores. Results: A total of 127 patients were enrolled in the OLE, with 74 (58.3%) completing the study. Treatment-emergent AEs (TEAEs) occurred in 73 patients (57.5%) with 54 (42.5%) experiencing a drug-related TEAE. TEAEs that occurred in ≥5% of patients were headache, dry mouth, dizziness, nausea, somnolence, anxiety, and irritability. Most TEAEs were mild or moderate in severity. Extrapyramidal-symptom-related TEAEs were rare. Most patients who had normal metabolic laboratory values at baseline remained normal during the treatment period. Mean changes in blood pressure, pulse rate, ECG, and body morphology were minimal. Symptoms of depression improved as measured by the mean change from baseline to Day 175 in MADRS Total score (−8.9) and CGI-BP-S Total score (−2.3). Conclusion: In patients with bipolar depression, long-term LUMA treatment was generally well tolerated with low risk of extrapyramidal symptoms, weight gain, and cardiometabolic effects. These data further support the safety, tolerability, and effectiveness of LUMA in patients with bipolar depression. Funding: Intra-Cellular Therapies, Inc.